Androgen receptor signaling and pyrethroids: Potential male infertility consequences - Sheikh, Ishfaq Ahmad; Beg, Mohd Amin; Hamoda, Taha Abo-AlmagdAbdel-Meguid; Mandourah, Hammam Mahmoud Siraj; Memili, Erdogan (Frontiers in Cell and Developmental Biology, 2023)
Infertility is a global health concern inflicting a considerable burden on the global economy and a severe socio-psychological impact. Approximately 15% of couples suffer from infertility globally, with a male factor contribution of approximately 50%. However, male infertility remains largely unexplored, as the burden of infertility is mostly assigned to female people. Endocrine-disrupting chemicals (EDCs) have been proposed as one of the factors causing male infertility. Pyrethroids represent an important class of EDCs, and numerous studies have associated pyrethroid exposure with impaired male reproductive function and development. Therefore, the present study investigated the potentially toxic effects of two common pyrethroids, cypermethrin and deltamethrin, on androgen receptor (AR) signaling. The structural binding characterization of cypermethrin and deltamethrin against the AR ligand-binding pocket was performed using Schrodinger’s induced fit docking (IFD) approach. Various parameters were estimated, such as binding interactions, binding energy, docking score, and IFD score. Furthermore, the AR native ligand, testosterone, was subjected to similar experiments against the AR ligand-binding pocket. The results revealed commonality in the amino acid-binding interactions and overlap in other structural parameters between the AR native ligand, testosterone, and the ligands, cypermethrin and deltamethrin. The estimated binding energy values of cypermethrin and deltamethrin were very high and close to those calculated for AR native ligand, testosterone. Taken together, the results of this study suggested potential disruption of AR signaling by cypermethrin and deltamethrin, which may result in androgen dysfunction and subsequent male infertility.